Acute Effects of Subthalamic Deep Brain Stimulation on Motor Outcomes in Parkinson's Disease; 13 Year Follow Up - Zhou, Haiyan; Wang, Linbin; Zhang, Chencheng; Qiu, Xian; Hu, Wei; van der Stelt, Odin; Ramirez-Zamora, Adolfo; Li, Dianyou (Frontiers in Neurology, 2019)
Objective: Deep brain stimulation of the Subthalamic nucleus (STN-DBS) is a safe and well established therapy for the management of refractory motor symptoms in Parkinson’s disease (PD). Marked improvement in axial symptoms has been reported in the short term with STN-DBS but questions remain regarding the long-term efficacy of this intervention. We assessed the acute ON and OFF effects of STN-DBS in PD patients who have been treated with STN-DBS for over a decade. Methods: We assessed 11 patients with early-onset PD (9 men, 2 women; mean age, 57.1 ± 7.2 y; mean age at illness onset, 38.9 ± 7.5 y) managed with long-term bilateral STN-DBS (mean treatment duration, 13.4 ± 1.3 y). Motor symptoms were assessed by means of the Unified Parkinson’s Disease Rating Scale (UPDRS)-III, Timed Up and Go test (TUG) and Hoehn-Yahr scale. Motor assessments in the medication ON and OFF states with stimulation ON and OFF conditions were documented and video recorded. Results: Patients showed a significantly improvement in motor symptoms both in the off-medication and on-medication state by a 54% reduction (off-medication/on-stimulation versus off-medication/off-stimulation) and a 48% reduction (on-medication/on-stimulation versus on-medication/off-stimulation) in the total UPDRS-III score. Specifically, Improvement in axial symptoms (off-medication: 51% reduction; on-medication: 44% reduction), including gait but not posture. Similarly, STN-DBS reduced TUG scores (off-medication: 70% reduction; on-medication: 47% reduction). Conclusions: On stimulation long-term, bilateral STN-DBS improves appendicular and axial symptoms of PD patients with young-onset and short duration at time of DBS in the acute setting.